Does screening shorten delays to care for post-deployment mental disorders in military personnel? A longitudinal retrospective cohort study. Issue 8 (20th August 2020) - Boulos, David; Garber, Bryan
Abstract : Objective: To determine whether post-deployment screening is associated with a shorter delay to diagnosis and care among individuals identified with a deployment-related mental disorder. Design: Retrospective cohort study. Setting: Canadian military population. Participants: The cohort consisted of personnel (n=28 460) with a deployment within the 2009 to 2014 time frame. A stratified random sample (n=3004) was selected for medical chart review. We restricted our analysis to individuals who had an opportunity to undergo screening and were subsequently diagnosed with a mental disorder that a clinician indicated was deployment-related (n=1157). Interventions: Post-deployment health screening. Main outcome measure: The outcome was delay to diagnosis and care, the latency from individuals' deployment return to their mental disorder diagnosis date. Cox proportional hazards regression assessed screening's influence on this outcome. Results: 74.4% of the study population had screened. Overall, the median delay to care was 766 days, 578 days among screeners and 928 days among non-screeners—a 350-day difference. Cox regression indicated that screeners had a significantly shorter delay to care (adjusted HR (aHR), 1.43 (95% CI, 1.11 to 1.86)). Screening findings had a substantial influence on delay to care. Identification of a mental health concern, whether a 'major' concern (aHR, 3.36 (95% CI, 2.38 to 4.73)) or a 'minor' concern (aHR, 1.46 (95% CI, 1.08 to 1.99)), and a recommendation for mental health services follow-up (aHR, 2.35 (95% CI, 1.73 to 3.21)) were strongly associated with shorter delays to care relative to non-screeners. Conclusions: Reduced delays to care are anticipated to lead to beneficial outcomes for both the individual and military organisation. We found that screening was associated with a shortened delay to care for mental disorders that were deployment-related. Future work will further explore this screening's components and optimisation strategies.